2015
DOI: 10.3390/md13095533
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Improves Human Sperm Capacitation by Inducing Lyn Displacement and Activation

Abstract: Astaxanthin (Asta), a photo-protective red pigment of the carotenoid family, is known for its multiple beneficial properties. In this study, the effects of Asta on isolated human sperm were evaluated. Capacitation involves a series of transformations to let sperm acquire the correct features for potential oocyte fertilization, including the generation of a controlled amount of reactive oxygen species (ROS), cholesterol depletion of the sperm outer membrane, and protein tyrosine phosphorylation (Tyr-P) process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…508 By combining virtual-and structure-based ligand screening approaches, a database of >100 caulerpin analogues was efficiently evaluated in silico for potential inhibitory activity against monoamine oxidase B, 509 while astaxanthin and other algal carotenoids have been the focus of many studies and reviews. [510][511][512][513][514][515][516][517][518]…”
Section: Green Algaementioning
confidence: 99%
“…508 By combining virtual-and structure-based ligand screening approaches, a database of >100 caulerpin analogues was efficiently evaluated in silico for potential inhibitory activity against monoamine oxidase B, 509 while astaxanthin and other algal carotenoids have been the focus of many studies and reviews. [510][511][512][513][514][515][516][517][518]…”
Section: Green Algaementioning
confidence: 99%
“…This carotenoid has a greater antioxidant activity than other carotenoids because of the hydroxyl and ketonic end groups located on the ionone rings of its chemical structure (Guerin, Huntley, & Olaizola, 2003). Reportedly, astaxanthin improves human sperm capacitation by increasing its activation (Andrisani et al, 2015). However, astaxanthin is highly susceptible to oxygen, light, and auto-oxidation (Vasantha, Rupasinghe, & Yasmin, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…9 Many recent studies considered statins as the potential therapeutic agent for a targeted conservative treatment of female gonadal function, fertility 10 endometriosis in humans 11 and reduced mortality among women affected by endometrial/ovarian malignancies. 12 Whereas Andrisani et al 13 found Astaxanthin (Asta), a photo-protective red pigment of the carotenoid family, utilized to decrease male idiopathic infertility. Studies from the authors' laboratory have demonstrated that insufficient local concentrations of glutathione may predispose tubular cells to damage by locally produced chloroacetaldehyde.…”
Section: Introductionmentioning
confidence: 99%